Optimasi Sintesis Biodiesel dari Minyak Biji Nyamplung (Calophyllum inophyllum) Melalui Reaksi Transesterifikasi Menggunakan Katalis TiO2 - Arlia, Erma; Gunawan, Erin Ryantin; Murniati, Murniati; Handayani, Sri Seno; Suhendra, Dedy (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Dependence on solar power needs can be overcome by switching to renewable energy, namely biodiesel. Biodiesel can be synthesized from non-food vegetable oil, namely nyamplung seed oil, with the help of a catalyst. The aim of this research is to optimize the synthesis of biodiesel from nyamplung seed oil through a transesterification reaction using a TiO2 catalyst. Variations in reaction conditions include the mole ratio of oil: methanol, catalyst mass, reaction time and reaction temperature. The optimum conditions for biodiesel synthesis were obtained at mole ratio of oil: methanol  1:8; catalyst 0.15 g; reaction time 150 minutes and reaction temperature 60℃ with an average yield of 76.54%. The characteristics of the biodiesel obtained include  0.877 g/mL of density, 3.65 cSt of viscosity,   234.217 mg KOH/g of saponification value, and 2.1 mg NaOH/g of acid value. The chemical composition of biodiesel resulting from GC-MS is methyl palmitate, methyl oleate and methyl stearate.